Assessing the Nature and Strategies used for Revenue Knowledge Development to support the Management of Public Revenue Mobilization in Pallisa District, Uganda - Moses Makoha Nasinyama; James Mugisha; Juma Sultan Kakuba (International Journal of Qualitative Research, 2026)
This paper assessed the nature and strategies used for revenue knowledge development to support the management of public revenue mobilization (PRM) in Pallisa District, Uganda. A descriptive case study design, which was purely qualitative, was adopted, with a diverse mix of study participants. Data was collected using an in-depth interview guide, a key informant interview guide, a focus group discussion guide, and a document review guide. Findings revealed the existence of both informal sources of revenue knowledge (conversations, vendor networks, or families and formal sources of revenue knowledge (books, magazines, brochures), and the existence of the Taxpayer Registration Expansion Program (TREP) arrangement between Uganda Revenue Authority (URA), Uganda Registration Services Bureau (URSB), Kampala Capital City Authority (KCCA), and Local Governments (LGs). The study concluded that building the capacity of the technical (revenue) officers, political leaders and the business community to obtain, refine and utilize revenue-related knowledge/information; ensure that technical (revenue) officers undertake sensitization efforts through training, meetings, ‘barazas’, and workshops to enlighten and provide revenue information pertinent to the business community and the Government of Uganda ensure that the Taxpayer Registration Expansion Program (TREP) arrangement between URA, URSB, KCCA, and LGs is strengthened and mandates harmonized to promote cooperation, coordination and implementation would support the management of the public revenue mobilization in Pallisa district and Uganda.